Fluoroscopy Dose and Time Characteristics During Endoscopic Retrograde Cholangiopancreatography (ERCP). Issue 1 (February 2019) - Syed, Aslam R.; Garg, Mrinal S.; Patel, Pikul; Singh, Shailendra; Blackwood, Margaret; Munigala, Satish; Thakkar, Payal; Farah, Katie; Aoun, Elie; Kulkarni, Abhijit; Dhawan, Manish; Agarwal, Satty; et al.
Abstract : Radiation exposure during endoscopic retrograde cholangiopancreatography is known, however, data in relation to radiation usage is unclear. We evaluate radiation exposure using fluoroscopy dose (FD) and time (FT). A prospective analysis of 197 patients undergoing endoscopic retrograde cholangiopancreatography was completed. Univariate and multivariate analyses were performed to determine characteristics associated with higher FD and FT. The mean FT was 307 seconds; the mean FD was 16.5 centigray. On univariate and multivariate analysis, indication of common bile duct stricture and pancreatic stricture, interventions including dilation and the use of plastic stents placement, procedures that were moderately or very difficult, and procedures that used magnification and high-resolution images were associated with higher FD± and longer FT. Indications of common bile duct stricture and pancreatic stricture as well as interventions of dilation, plastic stents placement, and procedures that are moderately or very difficult, involve high-resolution image leading to a higher radiation exposure. Special care should be considered in these settings.